Cesarean Section and Socioeconomic Status in Tehran, Iran - Omani-Samani, Reza (J Res Health Sci, 2017)
Background: Socioeconomic status (SES) is linked to a wide range of maternity services including Cesarean section (CS). The objective of this study was to determine the rate of CS and to examine the effect of SES on CS rate. Study design: Cross-sectional study. Methods: This study included 4308 pregnant women who gave singleton birth in Tehran, Iran in July 2015. To evaluate the effect of SES on CS, logistic regression model was used after adjusting for others variables. Results: The CS rate was 72.0% and its rate in private hospitals was significantly higher than in public hospitals (91.7 vs 62.6%, P<0.001). After adjusting for demographic characteristics of mothers, obstetrical data and newborn’s information, economic status (ES) was associated with an increased rate of CS (OR= 1.22; 95% CI=1.16–1.28). Conclusions: Independently of biological or clinical factors, ES is associated with an increased rate of CS in Tehran, Iran.